Right sided sigmoid colon and oblique descending colon with its embryological basis and clinical significance - Ashwini Nuchhi; Sandhya Yatagiri; R S Bulagouda (BLDE University Journal of Health Sciences, 2020)
Embryological development of the colon is complex and often unpredictable, leading to variations in the length and position. During routine dissection for undergraduate students in the Department of Anatomy, BLDE DU) Shri B. M. Patil Medical College and Research centre we found rare variations in the disposition of large intestine and inferior mesenteric artery in two male elderly cadavers. Case 1: The caecum and appendix were present in the right lumbar region, ascending colon is short, descending colon crossed the great vessels of the abdomen from left to right obliquely and sigmoid colon was present in the right iliac fossa below caecum and appendix. Inferior mesenteric artery arose from the right side of the ventral surface of the abdominal aorta to supply the left one-third of transverse colon, splenic flexure, descending colon, sigmoid colon. Case 2: same variations as in the first case with Sigmoid mesocolon adhered to mesentery near the ileocaecal junction. These variations may be helpful for the radiologists and Surgeons while undertaking an investigative or surgical procedure.